Nitrogen-coupled bimetallic modified artificial wetland matrix material and preparation method and application thereof
Through the preparation of nitrogen-coupled bimetal modified biochar material, the shortcomings of traditional matrix materials in the adsorption and degradation properties of pollutants are solved, and efficient removal of organic matter, total phosphorus and heavy metals in wastewater are achieved, which simplifies the preparation process and reduces the use of chemical reagents.
Patent Information
- Application Number
- CN202411864711.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing artificial wetland matrix materials have shortcomings in the adsorption and degradation properties of pollutants, and the traditional modification methods have defects such as complex process, long time consumption and large amount of chemical reagents.
Using the nitrogen-coupled bimetal modification method, a nitrogen-coupled aluminum/ferro modified biochar material is formed by polymerizing and crosslinking the biomass raw material with a nitrogen-containing compound, and then introducing aluminum and iron ions in the electrochemical reaction.
The removal rate of organic matter, total phosphorus and heavy metals in sewage by artificial wetlands has been significantly improved, the preparation process is simplified, and the use of chemical reagents is reduced.
Smart Images

Figure CN119320209B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sewage treatment, and specifically relates to a nitrogen-coupled bimetallic modified artificial wetland matrix material and a preparation method and application thereof. Background Art
[0002] Constructed wetlands are an engineering wetland technology that simulates natural wetland systems for wastewater treatment. They can be used to treat slightly polluted domestic sewage and industrial wastewater. They have the characteristics of convenient operation, maintenance and management, good treatment effect, low engineering infrastructure and operation costs, and strong adaptability to load changes. In addition, they can also have landscape appreciation functions like natural wetlands. As an indispensable part of artificial wetlands, the matrix is one of the main environmental entities of artificial wetlands. It is generally composed of gravel, sand, soil or other adsorption materials. The matrix of artificial wetlands is the basis for the survival of plants and microorganisms. It can provide a stable attachment surface for the growth of microorganisms and also provide growth support for plants in wetlands. In addition, the matrix is also the reaction site for most pollutants to undergo physical, chemical and biological reactions. Therefore, the selection of the matrix is the key to whether the wetland can achieve efficient pollutant removal.
[0003] Traditional matrix fillers, such as biochar, zeolite and coarse sand, have the disadvantages of limited adsorption capacity, re-release of pollutants, general saturation and weak chemical reactivity. Modifying traditional matrix to further improve the physical, chemical and biological synergy of wetland matrix and better remove pollutants from water bodies is one of the current research hotspots.
[0004] Metal loading modification of biochar is currently the most commonly used biochar modification method. Generally, a single metal oxide that can react with pollutants is introduced into biochar through physical and chemical methods, so that the new material has the strong binding ability of metal oxides and anions while maintaining the performance advantages of the original biochar material (Xiao Shuying. Preparation of modified biochar adsorption materials and study on their adsorption behavior for phosphorus [D]. Nanjing: Southeast University, 2021.; Duan Haonan, Lv Hong, Wang Fumei, et al. Research progress on the preparation of biochar / iron composite materials and their application in environmental remediation [J]. Environmental Chemistry, 2020, 39(3): 774-790.). For biochar modified with bimetallic materials, different types of metal ions may cause different changes in its physical configuration and surface properties during the preparation process. After preparation, the mixed (hydr)oxides containing different metals not only inherit the adsorption capacity of different single metal (hydr)oxides, but may also show the synergistic effect of bimetallic materials, further enhancing the adsorption and degradation performance of pollutants in mixed polluted water bodies, thereby improving the effect of artificial wetlands on pollutant purification. Commonly used methods include impregnation pyrolysis and coprecipitation, but the above methods have the defects of complex processes, long time consumption, and large amounts of chemical reagents. Therefore, it is of practical significance to develop a method that is simple to operate, fast and effective in preparing bimetallic modified biochar materials.
[0005] In recent years, nitrogen-doped modified biochar has shown strong adsorption capacity and excellent electrical conductivity. During pyrolysis, nitrogen-containing structures can better act on the biochar surface, causing changes in oxygen-containing and nitrogen-containing functional groups and pore structures on the biochar, especially the formation of delocalized π bonds in the carbon structure to increase surface active sites and hydrophilicity, thereby affecting the adsorption capacity of biochar. However, direct use of nitrogen-containing reagents for combination can easily cause biochar pore blockage, which will reduce the adsorption capacity of biochar (Ren Yanjiao, Xu Rongsheng, Wang Ping, et al. Adsorption performance of methylene blue on Lycium barbarum stem biochar modified by disodium oxalate tetraacetic acid [J]. Applied Chemistry, 2024, 41(7): 1035-1046).
[0006] Therefore, how to better embed nitrogen atoms and thus improve the surface physical properties and chemical reaction activity of the material is the key to improving the polarity of biochar and enhancing the adsorption capacity of biochar, and it is also a technical problem that needs to be solved urgently. Summary of the invention
[0007] In order to solve the above technical problems, the present invention first provides a method for preparing a nitrogen-coupled bimetallic modified artificial wetland matrix material.
[0008] The technical means adopted by the present invention are as follows:
[0009] A method for preparing a nitrogen-coupled bimetallic modified artificial wetland matrix material, wherein the matrix material is nitrogen-coupled aluminum / iron modified biochar, comprising the following steps:
[0010] S1. The biomass raw material is dried and ground into powder, and polymerized and cross-linked with a nitrogen-containing compound, and the cross-linked powder is dried and carbonized at a high temperature to obtain an N-doped precursor material;
[0011] S2. adding the N-doped precursor material to a NaCl solution to obtain an electrolyte, and performing a first direct current electrolysis reaction with an aluminum sheet as an anode and an iron sheet as a cathode to obtain a nitrogen-coupled aluminum-modified material;
[0012] S3. Replace the anode electrode with an iron sheet and perform a second direct current electrolysis operation to obtain a nitrogen-coupled aluminum / iron modified material, which is the desired matrix material.
[0013] Preferably, in step S1, the polymerization cross-linking method is to mix the biomass powder with epichlorohydrin and disodium ethylenediaminetetraacetate and stir evenly, adjust the pH value of the system to 8.0, and react in a water bath at 75-85° C. and stir for 60 min.
[0014] Preferably, the mixing ratio of the powder to epichlorohydrin and disodium ethylenediaminetetraacetate is 1 g: (2-3) ml: (10-15) g.
[0015] Preferably, in step S1, the polymerized and cross-linked powder is dried at 80°C to constant weight, then pyrolyzed at 450-550°C for 1 h, and then ground through a 0.2 mm sieve, and the sieve-through material is the carbonized N-doped precursor material.
[0016] Preferably, in step S2, the N-doped precursor material is added to a NaCl solution with a concentration of 10 mmol / L at a solid-liquid ratio of 1 g:50 ml to obtain an electrolyte.
[0017] Preferably, the surface area of one side of the electrode is 11-12 cm 2 , thickness 0.5~3 mm; in step S2, the first DC electrolysis reaction condition is to set the distance between the cathode and the anode to 8 cm, and apply 100 mA / cm 2 Current density, electrolysis time 30 min.
[0018] Preferably, in step S3, the second direct current electrolysis reaction conditions are as follows: NaBH4 with a mass concentration of 1% is added to the electrolyte, the distance between the cathode and the anode is set to 8 cm, and the current is 100 mA / cm 2 Current density, electrolysis time 30 min.
[0019] Preferably, after the second direct current electrolysis is completed, the precipitate is collected by filtration and centrifugation, washed and dried at 80° C. to constant weight to obtain the desired matrix material.
[0020] The present invention secondly provides a nitrogen-coupled bimetallic modified artificial wetland matrix material, and the matrix material is prepared using the preparation method as described above.
[0021] Preferably, the matrix material is biochar, and the matrix material is nitrogen-coupled aluminum / iron modified biochar, the particle size of the nitrogen-coupled aluminum / iron modified biochar is 0.15~0.25 mm, and the relative loading amounts of iron and aluminum are 0.42wt%±0.02wt% and 0.68wt%±0.01wt%, respectively.
[0022] The present invention again provides an application of the nitrogen-coupled bimetallic modified artificial wetland matrix material as described above in sewage treatment.
[0023] Preferably, the sewage treatment comprises preparing an artificial wetland for treating sewage and / or a sewage treatment system comprising an artificial wetland.
[0024] The beneficial effects of the present invention are as follows:
[0025] 1) Biomass raw materials include waste generated during agricultural production, such as fruit shells and straw generated during planting, which are usually treated as garbage. The present invention uses biomass as raw material, which has a wide source, is easy to collect, and is inexpensive. It can increase the added value of biomass raw materials, and waste utilization is also conducive to sustainable development.
[0026] 2) The preparation method of the matrix material is simple, the reaction environment is easy to achieve, and the steps of bimetallic modification can be carried out in the same reaction cell, which is simple to operate and saves time and effort.
[0027] 3) This method first reconstructs the biochar surface by a nucleophilic substitution reaction between epichlorohydrin and the hydroxyl groups on the biochar surface, then adds disodium ethylenediaminetetraacetic acid to undergo a substitution reaction on the biochar carbon surface to introduce nitrogen, and then couples the metal ion distribution to the biochar material under the action of an electrochemical reaction. Since the chelation of nitrogen and metals is more conducive to the formation of a stable structure of the metals used on the biochar surface, the matrix material can more sustainably exert its adsorption effect on pollutants, and can effectively improve the organic pollutants (COD), total phosphorus (TP) and heavy metal copper (Cu) in sewage. 2+ The prepared matrix material is used in artificial wetlands, which can significantly improve the comprehensive purification capacity of sewage on the basis of the purification of the original ordinary biochar matrix. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1The present invention discloses a preparation process of the nitrogen-coupled bimetallic modified artificial wetland matrix material.
[0029] Figure 2 This is an electron microscope scanning image of the nitrogen-coupled bimetallic modified artificial wetland matrix material prepared in Example 1, in which a is the surface of ordinary biochar, and b is the surface of the nitrogen-coupled bimetallic modified artificial wetland matrix material.
[0030] Figure 3 This is the EDS spectrum analysis result of the nitrogen-coupled bimetallic modified artificial wetland matrix material prepared in Example 1.
[0031] Figure 4 These are the results of the shake flask experiment in Experiment 1.
[0032] Figure 5 Schematic diagram of the device used to simulate the artificial wetland system prepared in Experiment 2.
[0033] Figure 6 This is the COD (organic pollutants) treatment status of sewage in Experiment 2.
[0034] Figure 7 This is the TP (total phosphorus) treatment of sewage in Experiment 2.
[0035] Figure 8 is the heavy metal copper (Cu 2+ ) handling the situation. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is described in more detail below in conjunction with the embodiments.
[0037] Example 1
[0038] See also Figure 1 The process shown is a method for preparing a nitrogen-coupled bimetallic modified artificial wetland matrix material, comprising the following steps:
[0039] S1. Grind the biomass into powder. The biomass used in this embodiment is peanut shells; wash and grind the peanut shells, and screen the powder with a particle size of less than 0.2 mm; stir 100 g of the screened powder with 200 ml of epichlorohydrin (99.5%) and 1000 ml of disodium ethylenediaminetetraacetate, adjust the pH value of the system to about 8.0, and stir the reaction in a water bath at 75-85°C for 60 min to complete the N-doping process and obtain N-doped powder;
[0040] The N-doped powder was filtered out, washed three times with anhydrous ethanol and deionized water, dried in an oven at 80°C to constant weight, and then pyrolyzed at 450-550°C for 1 h in a muffle furnace to obtain a carbonized N-doped precursor material.
[0041] S2. The prepared precursor material was added to a NaCl solution having a concentration of 10 mmol / L according to 1 g: 50 ml to obtain an electrolyte;
[0042] Iron and aluminum were used to prepare the single-side surface area of 11.25 cm 2 The electrode sheet was placed vertically in the electrolyte with the aluminum sheet as the anode and the iron sheet as the cathode for the first electrolysis operation. In the first electrolysis operation, the distance between the cathode and the anode was about 8 cm, and 100 mA / cm was applied to the electrode. 2 The current density was 30 min and the electrolysis time was 30 min to obtain the nitrogen-coupled aluminum-modified material;
[0043] S3. After the first electrolysis is completed, the anode electrode is replaced with an iron sheet, and the electrode is placed vertically in the electrolyte for the second electrolysis operation. In the second electrolysis operation, 1% NaBH4 is added to the electrolyte, the distance between the cathode and the anode is 8 cm, and 100 mA / cm is applied to the electrode. 2 The current density was 30 min and the electrolysis time was 30 min to obtain nitrogen-coupled aluminum / iron modified biochar;
[0044] After the second electrolysis is completed, the precipitate is collected by filtration and centrifugation, washed, dried and placed in an environment of 80° C. to dry to constant weight, thereby obtaining the desired nitrogen-coupled aluminum / iron-modified matrix material.
[0045] Figure 2 This is a SEM comparison of the biochar formed by pyrolysis of peanut shells and the nitrogen-coupled aluminum / iron modified biochar prepared by this method. It can be seen that the biochar formed by pyrolysis of peanut shells is porous and has a relatively flat and smooth surface, while the nitrogen-coupled aluminum / iron modified biomatrix material prepared by the invention has attachments in the pores and a rough surface. The surface of the prepared nitrogen-coupled aluminum / iron modified biomatrix material is also loaded with metal elements such as iron and aluminum. The results of EDS energy spectrum analysis can be found in Figure 3 The relative loading amounts of iron and aluminum are approximately 0.42wt%±0.02wt% and 0.68wt%±0.01wt%.
[0046] Example 2
[0047] A method for preparing a nitrogen-coupled bimetallic modified artificial wetland matrix material comprises the following steps:
[0048] S1. Grind the biomass into powder. The biomass used in this embodiment is peanut shells; wash and grind the peanut shells, and screen the powder with a particle size of less than 0.2 mm; stir 100 g of the screened powder with 100 ml of epichlorohydrin (99.5%) and 1000 ml of disodium ethylenediaminetetraacetic acid reagent, adjust the pH value of the system to about 8.0, and stir the reaction in a water bath at 75-85°C for 60 min to complete the N-doping process and obtain N-doped powder;
[0049] The N-doped powder was filtered out, washed three times with anhydrous ethanol and deionized water, dried in an oven at 80°C to constant weight, and then pyrolyzed at 450-550°C for 1 h in a muffle furnace to obtain a carbonized N-doped precursor material.
[0050] S2. The prepared precursor material was added to a NaCl solution having a concentration of 10 mmol / L according to 1 g: 25 ml to obtain an electrolyte;
[0051] Iron and aluminum were used to prepare 2 , 2 mm thick electrode sheet, aluminum sheet as anode, iron sheet as cathode, the electrode was placed vertically in the electrolyte, and the first electrolysis operation was carried out. In the first electrolysis operation, the distance between the cathode and the anode was about 8 cm, and 100 mA / cm was applied to the electrode. 2 The current density was 30 min and the electrolysis time was 30 min to obtain the nitrogen-coupled aluminum-modified material;
[0052] S3. After the first electrolysis is completed, the anode electrode is replaced with an iron sheet, and the electrode is placed vertically in the electrolyte for the second electrolysis operation. In the second electrolysis operation, 1% NaBH4 is added to the electrolyte, the distance between the cathode and the anode is 8 cm, and 100 mA / cm is applied to the electrode. 2 The current density was 30 min and the electrolysis time was 30 min to obtain nitrogen-coupled aluminum / iron modified biochar;
[0053] After the second electrolysis is completed, the precipitate is collected by filtration and centrifugation, washed, dried and placed in an environment of 80° C. to dry to constant weight, thereby obtaining the final nitrogen-coupled aluminum / iron-modified matrix material.
[0054] Example 3
[0055] A method for preparing a nitrogen-coupled bimetallic modified artificial wetland matrix material comprises the following steps:
[0056] S1. Grind the biomass into powder. The biomass used in this embodiment is walnut shells; clean and grind the walnut shells, and screen the powder with a particle size of less than 0.2 mm; stir 100 g of the screened powder with 200 ml of epichlorohydrin (99.5%) and 1000 ml of disodium ethylenediaminetetraacetate, adjust the pH value of the system to about 8.0, and stir the reaction in a water bath at 75-85°C for 60 min to complete the N-doping process and obtain N-doped powder;
[0057] The N-doped powder was filtered out, washed three times with anhydrous ethanol and deionized water, dried in an oven at 80°C to constant weight, and then pyrolyzed at 450-550°C for 1 h in a muffle furnace to obtain a carbonized N-doped precursor material.
[0058] S2. The prepared precursor material was added to a NaCl solution having a concentration of 100 mmol / L at a ratio of 1 g: 100 ml to obtain an electrolyte;
[0059] With the aluminum sheet as the anode and the iron sheet as the cathode, the electrodes were placed vertically in the electrolyte for the first electrolysis operation. In the first electrolysis operation, the distance between the cathode and the anode was about 8 cm, and 100 mA / cm was applied to the electrodes. 2 The current density was 40 min and the electrolysis time was 40 min to obtain the nitrogen-coupled aluminum-modified material;
[0060] S3. After the first electrolysis is completed, the anode electrode is replaced with an iron sheet, and the electrode is placed vertically in the electrolyte to perform the second electrolysis operation. In the second electrolysis operation, the distance between the cathode and the anode is 8 cm, and 100 mA / cm is applied to the electrode. 2 The current density was 40 min and the electrolysis time was 40 min to obtain nitrogen-coupled aluminum / iron modified biochar;
[0061] After the second electrolysis is completed, the precipitate is collected by filtration and centrifugation, washed, dried and placed in an environment of 80° C. to dry to constant weight, thereby obtaining the final nitrogen-coupled aluminum / iron-modified matrix material.
[0062] Comparative Example 1
[0063] The preparation method of nitrogen-coupled single metal modified artificial wetland matrix material comprises the following steps:
[0064] S1. Grind the biomass into powder. The biomass used in this embodiment is peanut shells; wash and grind the peanut shells, and screen the powder with a particle size of less than 0.2 mm; stir 100 g of the screened powder with 200 ml of epichlorohydrin (99.5%) and 1000 ml of disodium ethylenediaminetetraacetate, adjust the pH value of the system to about 8.0, and stir the reaction in a water bath at 75-85°C for 60 min to complete the N-doping process and obtain N-doped powder;
[0065] The N-doped powder was filtered out, washed three times with anhydrous ethanol and deionized water, dried in an oven at 80°C to constant weight, and then pyrolyzed at 450-550°C for 1 h in a muffle furnace to obtain a carbonized N-doped precursor material.
[0066] S2. The prepared precursor material was added to a NaCl solution having a concentration of 10 mmol / L according to 1 g: 50 ml to obtain an electrolyte;
[0067] Iron and aluminum were used to prepare 2 The electrode sheet is placed vertically in the electrolyte with the aluminum sheet as the anode and the iron sheet as the cathode for electrolysis. During the electrolysis, the distance between the cathode and the anode is about 8 cm, and 100 mA / cm is applied to the electrode. 2 The current density was 25 min and the electrolysis time was 25 min to obtain nitrogen-coupled aluminum-modified biochar;
[0068] After the electrolysis is completed, the precipitate is collected by filtration and centrifugation, washed, dried and placed in an environment of 80° C. to dry to constant weight to obtain the final aluminum-modified matrix material.
[0069] Experiment 1
[0070] Shake flask experiments were carried out using unmodified peanut shell biochar (peanut shell powder material pyrolyzed at 450-550°C for 1 h), the single metal aluminum modified peanut shell biochar prepared in Comparative Example 1, and the nitrogen-coupled aluminum / iron modified biochar material prepared in Example 1 of the present application to determine the adsorption capacity of different materials for phosphorus.
[0071] Prepare 200 mL of 30 mg / L phosphorus solution and put it into a 500 mL conical flask. Add 0.15 g of the three adsorbent materials mentioned above into the conical flask respectively. Oscillate at 25°C and 100 rpm for 1 h. Filter the adsorbents through filter paper to remove the adsorbents and collect the filtrates. Use ammonium molybdate spectrophotometry to determine the phosphorus content in the three groups of filtrates, and calculate the adsorption amount of phosphorus by the adsorbent.
[0072] Results Figure 4The nitrogen-coupled aluminum / iron modified biochar material provided in this application has an adsorption capacity for phosphorus that is 1.23 times higher than that of unmodified peanut shell biochar and 27.8% higher than that of single metal aluminum modified peanut shell biochar.
[0073] Experiment 2
[0074] Vertical flow type artificial wetlands were prepared using the prepared nitrogen-coupled aluminum / iron modified matrix materials.
[0075] See also Figure 5 The artificial wetland simulation system device uses a PVC column with a height of 70 cm and an inner diameter of 25 cm, and the bottom of the column is set as a water outlet. The control group column is filled with a 15 cm thick coarse gravel layer (particle size 28-36 mm), a 25 cm thick medium gravel layer (particle size 8-18 mm), a 5 cm thick sand and gravel layer (particle size 2-4 mm), a 10 cm thick unmodified biochar matrix (peanut shell powder material pyrolyzed at 450-550 ° C for 1 h), and a 5 cm thick sand and gravel layer (particle size 2-4 mm) from the bottom to the top; the setting of the experimental group is the same as that of the control group, except that the unmodified biochar matrix in the control group is replaced by the biomatrix prepared in Example 2 and Comparative Example 1. Four water celery plants were planted on the upper layer of the simulation system.
[0076] The influent is sewage that exceeds the national sewage discharge standard: COD 150 mg / L, TP 10 mg / L, Cu 2+ 20mg / L.
[0077] Water is evenly distributed above the artificial wetland. The wastewater inlet volume of each column is 6 L, the flow rate is 1-3 mL / min, and the intermittent operation mode is adopted. The hydraulic retention time after each water inlet is 3 days. During the operation of the artificial wetland, water is taken and sampled at around 18:00 every day.
[0078] The artificial wetland system was run three times for a total of nine days. The effluent samples were tested for COD, TP, and Cu using a chemical analyzer within 24 hours. 2+ .
[0079] result
[0080] See also Figure 6 - Figure 8 The COD removal rate of the artificial wetland system containing ordinary biochar matrix was 54.92%, the TP removal rate was 71.63%, and the Cu 2+ The removal rate was 69.68%, and the average concentrations of effluent were COD 67.6 mg / L, TP 2.84 mg / L, Cu 2+ 6.06 mg / L.
[0081] The artificial wetland system using the nitrogen-coupled aluminum / iron modified matrix material prepared by the present invention has a COD removal rate of 82.13%, an average TP removal rate of 85.92%, and a Cu 2+ The removal rate was 91.92%, and the average concentrations of effluent were COD 26.8 mg / L, TP 1.41 mg / L, Cu 2+ 1.62 mg / L, the effluent COD meets the Class A standard of the Integrated Discharge Standard for Urban Sewage (GB18918-2002), and the effluent TP meets the Class B standard of the Integrated Discharge Standard for Urban Sewage (GB18918-2002).
[0082] Experiments show that the nitrogen-coupled aluminum / iron-modified matrix material can effectively improve the organic pollutants (COD), total phosphorus (TP) and heavy metal copper (Cu 2+ ) and other removal rates.
[0083] The above implementation modes are only used to illustrate the technical solutions of the present invention, but not to limit the present invention. Although the present invention has been described in detail with reference to the above implementation modes, those skilled in the art should understand that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a nitrogen-coupled bimetallic modified artificial wetland matrix material, characterized in that: The matrix material is nitrogen-coupled aluminum / iron modified biochar, comprising the following steps: S1. The biomass raw material is dried and ground into powder, and polymerized and cross-linked with a nitrogen-containing compound, and the cross-linked powder is dried and carbonized at a high temperature to obtain an N-doped precursor material; The polymerization cross-linking method comprises mixing the biomass powder with epichlorohydrin and disodium ethylenediaminetetraacetate, stirring the mixture evenly, adjusting the pH value of the system to 8.0, and reacting the mixture in a water bath at 75 to 85° C. and stirring the mixture for 60 minutes; S2. adding the N-doped precursor material to a NaCl solution to obtain an electrolyte, and performing a first direct current electrolysis reaction with an aluminum sheet as an anode and an iron sheet as a cathode to obtain a nitrogen-coupled aluminum-modified material; S3. Replace the anode electrode with an iron sheet and perform a second direct current electrolysis operation to obtain nitrogen-coupled aluminum / iron modified biochar, which is the desired matrix material.
2. The method for preparing the nitrogen-coupled bimetallic modified artificial wetland matrix material according to claim 1, characterized in that: The mixing ratio of the biomass powder to epichlorohydrin and disodium ethylenediaminetetraacetate is 1 g: (2-3) ml: (10-15) g.
3. The method for preparing the nitrogen-coupled bimetallic modified artificial wetland matrix material according to claim 1, characterized in that: In the step S1, the polymerized and cross-linked powder is dried at 80°C to a constant weight, then pyrolyzed at 450-550°C for 1h, and then ground through a 0.2mm sieve, and the sieved material is the carbonized N-doped precursor material.
4. The method for preparing the nitrogen-coupled bimetallic modified artificial wetland matrix material according to claim 1, characterized in that: In the step S2, the N-doped precursor material is added to a NaCl solution with a concentration of 10 mmol / L according to a solid-liquid ratio of 1 g:50 ml to obtain an electrolyte.
5. The method for preparing the nitrogen-coupled bimetallic modified artificial wetland matrix material according to claim 1, characterized in that: The surface area of the electrode on one side is 11 to 12 cm 2 , thickness 0.5-3 mm, in step S2, the first direct current electrolysis reaction conditions are: setting the distance between the cathode and the anode to 8 cm, applying 100 mA / cm 2 The current density and electrolysis time were 30 min. In step S3, the second direct current electrolysis reaction conditions were as follows: NaBH4 with a mass concentration of 1% was added to the electrolyte, the distance between the cathode and the anode was set to 8 cm, and the current to the electrode was 100 mA / cm 2 Current density, electrolysis time 30min.
6. The method for preparing the nitrogen-coupled bimetallic modified artificial wetland matrix material according to claim 1, characterized in that: After the second direct current electrolysis is completed, the precipitate is collected by filtration and centrifugation, washed and dried at 80° C. to constant weight to obtain the desired matrix material.
7. A nitrogen-coupled bimetallic modified artificial wetland matrix material, prepared using the preparation method described in any one of claims 1 to 6.
8. The nitrogen-coupled bimetallic modified artificial wetland matrix material according to claim 7, characterized in that: The matrix material is nitrogen-coupled aluminum / iron modified biochar, the particle size of the nitrogen-coupled aluminum / iron modified biochar is 0.15-0.25 mm, and the relative loading amounts of iron and aluminum are 0.42 wt%±0.02 wt% and 0.68 wt%±0.01 wt% respectively.
9. Use of the nitrogen-coupled bimetallic modified artificial wetland matrix material as claimed in claim 7 or 8 in sewage treatment, wherein the sewage treatment comprises preparing an artificial wetland for treating sewage and / or a sewage treatment system comprising an artificial wetland.
Citation Information
Patent Citations
Preparing method for nitrogen-doped porous carbon material, catalyst comprising material and application of material
CN104689857A
Electrolysis modified biomass charcoal system and application thereof
CN108249548A
Aluminum-iron double-metal modified biochar phosphorus removal material and preparation method thereof
CN114405471A